Determination and application of outdoor thermal benchmarks. (October 2017) - Cheung, Pui Kwan; Jim, C.Y.
Abstract: Neutral temperature, preferred temperature, acceptable temperature range, comfortable temperature range and neutral temperature range are commonly determined and applied in empirical outdoor thermal comfort studies. These attributes are important benchmark levels and ranges for urban planners to develop strategies to optimise outdoor thermal environment according to the requirements of the users. Since there is no guideline on how these levels and ranges should be defined and determined, significant variations of methods and terms exist in the literature. Many of the studies used the terms interchangeably, showing misconceptions and loose or inconsistent application of the cognate concepts. There is an urgent need to review the methods and terms used in these studies, clarify the misconceptions, and recommend methods to correctly determine and define the benchmark levels and ranges. In this study, we reviewed 24 recent empirical outdoor thermal studies, which reported at least one of the above five benchmarks. We identified that a neutral condition or an acceptable condition is often mistakenly assumed to be a comfortable condition. This assumption is not necessarily true because there is clear evidence that people prefer a temperature that is different from their neutral temperature . A conceptual framework of the human thermal environment was constructed to illustrate and clarify the interrelationships of these benchmarks. After a thorough review of the existing understanding and practices, a package of analytical methods was recommended and explained to determine neutral temperature, preferred temperature, acceptable temperature range and neutral temperature range . Highlights: Thermal benchmarks of outdoor thermal comfort are important for urban planning. Misconceptions on thermal benchmarks are discussed and clarified. Neutral condition is often mistakenly assumed or used as comfortable condition. Key relationships amongst the benchmarks are depicted in a synoptic diagram. Analytical methods are proposed to determine four important benchmarks.